A phylogenomic rodent tree reveals the repeated evolution of masseter architectures - Swanson, Mark T. (Proc Biol Sci, 2019)
Understanding the number of times a trait has evolved is a necessary foundation for comprehending its potential relationships with selective regimes, developmental constraints and evolutionary diversification. Rodents make up over 40% of extant mammalian species, and their ecological and evolutionary success has been partially attributed to the increase in biting efficiency that resulted from a forward shift of one or two portions of the masseter muscle from the zygomatic arch onto the rostrum. This forward shift has occurred in three discrete ways, but the number of times it has occurred has never been explicitly quantified. We estimated an ultrametric phylogeny, the first to include all rodent families, using thousands of ultraconserved elements. We examined support for evolutionary relationships among the five rodent suborders and then incorporated relevant fossils, fitted models of character evolution, and used stochastic character mapping to determine that a portion of the masseter muscle has moved forward onto the rostrum at least seven times (with one reversal) during the approximately 70 Myr history of rodents. Combined, the repeated evolution of this key innovation, its increasing prevalence through time, and the species diversity of clades with this character underscores the adaptive value of improved biting efficiency and the relative ease with which some advantageous traits arise.